Endoplasmic reticulum stress induced by tunicamycin increases resistin messenger ribonucleic acid through the pancreatic endoplasmic reticulum eukaryotic initiation factor 2α kinase–activating transcription factor 4–CAAT/enhancer binding protein‐α homologous protein pathway in THP‐1 human monocytes. Issue 3 (18th November 2015) - Hamada, Junpei; Onuma, Hiroshi; Ochi, Fumihiro; Hirai, Hiroki; Takemoto, Koji; Miyoshi, Akiko; Matsushita, Manami; Kadota, Yuko; Ohashi, Jun; Kawamura, Ryoichi; Takata, Yasunori; Nishida, Wataru; et al.
Abstract: Aims/Introduction: Resistin, secreted from adipocytes, causes insulin resistance in mice. In humans, the resistin gene is mainly expressed in monocytes and macrophages. Tunicamycin is known to induce endoplasmic reticulum (ER) stress, and reduce resistin gene expression in 3T3‐L1 mouse adipocytes. The aim of the present study was to examine whether ER stress affects resistin gene expression in human monocytes. Materials and Methods: The relationship between resistin messenger ribonucleic acid (mRNA) and ER stress markers mRNA was analyzed by reverse transcription polymerase chain reaction in isolated monocytes of 30 healthy volunteers. The effect of endotoxin/lipopolysaccharides or tunicamycin on resistin gene expression was analyzed in THP‐1 human monocytes. Signaling pathways leading to resistin mRNA were assessed by the knockdown using small interfering RNA or overexpression of key molecules involved in unfolded protein response. Results: Resistin mRNA was positively associated with immunoglobulin heavy chain‐binding protein (BiP) or CAAT/enhancer binding protein‐α homologous protein (CHOP) mRNA in human isolated monocytes. In THP‐1 cells, lipopolysaccharides increased mRNA of BiP, pancreatic endoplasmic reticulum eukaryotic initiation factor 2α kinase (PERK) and CHOP, as well as resistin. Tunicamycin also increased resistin mRNA. This induction appeared to be dose‐ and time‐dependent. Tunicamycin‐induced resistin mRNA was inhibited by chemical chaperone, 4‐phenylbutyric acid. The knockdown of either PERK, activating transcription factor 4 (ATF4) or CHOP reduced tunicamycin‐induced resistin mRNA. Conversely, overexpression of ATF4 or CHOP increased resistin mRNA. Conclusions: Endoplasmic reticulum stress induced by tunicamycin increased resistin mRNA through the PERK–ATF4–CHOP pathway in THP‐1 human monocytes. ER stress could lead to insulin resistance through enhanced resistin gene expression in human monocytes.